Evaluation of the efficacy of postmortem human bladder tissue as a normal comparator for case‐controlled gene expression studies in urology. Issue 4 (19th August 2016) - Matthews, Catherine A.; Eschenroeder, Andrew; Badlani, Gopal; Evans, Robert; Walker, Stephen J.
Abstract : AIMS: Interstitial cystitis/bladder pain syndrome (IC/BPS) is a poorly understood disease with no absolute diagnostic marker. A molecular‐based tool (biomarker) for IC/BPS diagnosis would have immediate clinical utility. We have generated a bank of bladder biopsy tissue from IC/BPS patients and require a control group for comparative gene expression studies. The objective of this pilot study was to investigate the feasibility of cadaveric bladder specimens as a viable source of control tissue. METHODS: Cryopreserved cadaveric bladder specimens were obtained through the National Disease Research Interchange (NDRI) tissue repository. Decedent demographics, postmortem interval to autopsy, necropsy location and size were recorded. At least two punch biopsies were taken from each bladder sample and total RNA was extracted. Nucleic acid concentration and quality were measured as was the RNA integrity number (RIN). RESULTS: We purchased 15 necropsy bladder specimens that had been harvested from women postmortem and flash‐frozen. For each bladder specimen, RNA was isolated from multiple sites for comparison both within and between individuals. Bioanalyzer results revealed severe degradation in the majority of samples as indicated by RINs ranging from "n/a" to 6.6, with most samples yielding RINs ≤2.5. Shorter postmortem interval did not correlate with an increase in RNA quantity or quality. CONCLUSIONS: Cadaver‐derived bladder tissue from the NDRI does not routinely yield high‐quality RNA needed for downstream gene expression applications, such as microarray and next‐generation sequencing and, therefore, cannot be used as a reliable source for control samples.